Effectiveness Learning Derivative On Period The Covid-19 Pandemic Through Mobile Learning Media in View of the Results Study STKIP student Hermon Timika - Rasul, A.; Sutirta, Habibi (Jurnal Pendidikan Dewantara, 2022)
The education system is faced with a situation that requires teachers to be able to mastering distance learning media, such as during the Covid-19 pandemic outbreak . The distance education system is one of the solutions to overcome internal difficulties face-to-face learning with the existence of social distancing rules which is an obstacle big moment This. Mobile Learning (M-Learning) is paradigm learning utilise technology And device Mobile Which estimated will experience development rapidly And potential along with development technology that mobile Alone. M-Learning is one of the learning media easy remote and often used for. This study aims to see the effectiveness of Derivative learning with use media M-Learning reviewed from results Study student. Model study Which used on study This is quasi experiment with use one group pretest postest design . Sample study that is student semester 2 Which take subject calculus. Data sample processed with analysis descriptive And test the average difference in learning outcomes. The results of the study show the course lectures calculus derived material using M-Learning media is quite effective if you look at it from results Study student. Results Study student after lectures with use M-Learning more tall compared to with results Study student before lectures with use M-Learning .